Motivation in the First Year of Nursing Education: It's Relationship with Professional Self-Concept, Self-Esteem - Feride Taskin Yilmaz; Selma Sabancıoğulları; Azime Karakoc Kumsar (Archives of Nursing Practice and Care - Peertechz Publications, 2016)
Aim: Motivation is one of the processes that initiates the effectiveness of learning. The study was conducted in order to examine the motivation levels of nursing students in their first year and the relationships between motivation levels and professional self-concept and self-esteem levels, as well as determining the personal and occupational characteristics that affect motivation. Methods: A total of 242 students participated in the descriptive and relational study. Data was collected using a student identification form, the Motivation Sources and Problems Scale (MSPS), the Professional Self Concept in Nursing Students Scale (PSCNSS), and the Stanley Coopersmith Self Esteem Scale (SCSES). In statistical evaluation, frequency, mean, the t test, the Pearson correlation analysis, the Stepwise Multiple Regression analysis, ANOVA, and the Kruskal Wallis test were used. Results: In the study, a positive, medium level significant relationship between MSPS general score averages and PSCNSS and SCSSRS general score averages was found (r=.44-.63; p<0.001) The MSPS general score averages of students who selected nursing voluntarily, didn't want to receive any other training than nursing, and thought positively regarding the future of their occupation were found to be significantly higher compared to other students (p<0.005). Conclusion: The motivation, professional self and self-esteem levels of the students were positive, and there was a positive medium level significant relationship between motivation levels and professional self and self-esteem levels. The motivation levels of students who had information and awareness regarding the occupation, and thought positively regarding the occupation were higher and more positive.